Cybersecurity Audit in the Small and Medium-Sized Enterprises - Magzumov, Timur (2020)
This work aims to find an answer to the following questions “What is the role of cybersecurity in modern SMEs?” and “What are the benefits of adopting SMESEC cybersecurity framework for European SMEs?”. This work is composed of eleven chapters, each of which deals with different aspects of cybersecurity in small and medium-sized organizations. The theoretical part of the research is concentrated on the topic of cybersecurity, and it's importance in the modern business world. Here presented the history and various methodologies to protect organizations from external threats. SMESEC cybersecurity framework has been chosen as a basis for the practical aspect of the current work. It presents the analysis of SMESEC, and it's advantages and possible adoption to European SMEs. Data for this thesis was collected by analysis of primary and secondary data. The research findings show that contemporary small and medium-sized enterprises cannot operate without the application of the latest cybersecurity practices.